Utilization of MIMO Concept for Optical Communication System under Fog Condition - Shakir, Farouk; Ali, Mazin Ali A.; Ameer, Firas (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
Free-space optical (FSO) communication consider license free, high data rate, wide bandwidth and cost-effective. Multi-input Multi-output (MIMO) systems can be employed to reduce the attenuation by heavy fog and improve FSO channel capacity. In this paper a single-input single-output and multi–input multi-output examined to investigate the performance of these systems under heavy fog. A comparison is made in terms of received optical power, signal to noise ratio, and bit error rate (BER) using OptiSystem version 7.0. The signal reaches to link up to 1.7km, 1.55km, 1.5km, and 1.4km for 4Tx/4Rx, 3Tx/3Rx, 2Tx/2Rx, 1Tx/1Rxrespectively. The results showed that the quality of received power is enhancement by using up to four beams.